The ecological footprint of pet dogs and cats (Revista Científica Ciencias Naturales y Ambientales, 2022)
As an indicator of sustainable development, the ecological footprint has succeeded in providing a basis for discussing the environmental impacts of human consumption. Human beings are the origin of numerous polluting activities on Earth and are the main drivers of climate change. However, very little research has been done on the environmental impacts of animals, especially domestic animals, such as dogs and cats, who require significant amounts of food to maintain their daily energy needs. Therefore, the dietary animal ecological footprint (AEF) could serve as a useful indicator to assess the impacts of pets on the environment. In this article, we explain the environmental impact of pet dogs and cats by quantifying their HEA and greenhouse gas (GHG) emissions according to primary data collected in the three districts of the city of Guayaquil in coordination with the faculty. of Veterinary Medicine and Zootechnics of the University of Guayaquil and of the Animal Welfare Unit of the Mayor’s Office of Guayaquil; The results show that the dietary EER of companion dogs and cats on commercial dry food in District 3 or District 1 was approximately twice that of District 2. It is concluded that the majority of companion dogs and cats in districts 1, 2 and 3 of Guayaquil they consume more energy than they really need to maintain normal activity, which affects GHG emissions and HEA from the diet.
Keywords: AEF; GHG; Enviroment; Animals; Pets; Guayaquil